Proteome changes of sheep rumen epithelium during postnatal development - Zheng, Kaizhi; Guo, Liangyong; Ullah, Saif; Cao, Yang; Huang, Xin; shan, Huili; Jiang, Junfang; Wu, Jianliang; Jiang, Yongqing (Frontiers in Genetics, 2022)
Background: The development of the rumen epithelium is a critical physiological challenge for sheep. However, the molecular mechanism underlying postnatal rumen development in sheep remains rarely understood. Results: Here, we used a shotgun approach and bioinformatics analyses to investigate and compare proteomic profiles of sheep rumen epithelium tissue on day 0, 15, 30, 45 and 60 of age. A total of 4523 proteins were identified, in which we found 852, 342, 164 and 95 differentially expressed proteins (DEPs) between D0 and D15, between D15 and D30, between D30 and D45, between D45 and D60, respectively. Furthermore, subcellular localization analysis showed that the DEPs were majorly localized in mitochondrion between D0 and D15, after which nucleus proteins were the most DEPs. Finally, Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) analyses showed that DEPs significantly enriched in mitochondrion, ubiquitination, histone modifications, glutathione synthase activity, and wnt and nortch signaling pathways. Conclusion: Our data indicate that the biogenesis of mitochondrion in rumen epithelial cell is essential for the initiation of rumen epithelial development. Glutathione, wnt signaling pathway and nortch signaling pathway participated in rumen epithelial growth. Ubiquitination, post-translational modifications of histone might be key molecular functions in regulating rumen epithelial development.